Optimizing The War Of Parents, Teachers And Children In An Effort To Improve Children's Learning During The Covid-19 Pandemic - Purba, Christopher A.P; Setiawati , Yunias (Jurnal Health Sains, 2023)
Children have the right to learn because it is the human right of every child to obtain proper education and teaching in the context of self-development in accordance with their interests and talents. The world of education is currently experiencing a major test due to the COVID-19 pandemic, because it has caused a crisis in the world of education. The COVID-19 pandemic has caused governments of countries around the world to close schools with the aim of inhibiting the transmission of the virus. Closing schools and learning from home through online has created its own challenges and obstacles for every child and teenager. Changes in the education system plus psychological problems experienced by children greatly affect the interest in learning of children and adolescents during the pandemic, where this can cause a child's academic achievement to decline. Distance learning from home expects the role of parents to be a bridge between teachers and children. Parents and teachers are also expected to be able to increase their respective roles and synergize with each other in increasing children's interest in learning during the COVID-19 pandemic